Trained immunity in diabetes: emerging targets for cardiovascular complications - Bai, Yanan; Wu, Jianglan; Jian, Weixiong (Frontiers in Endocrinology, 2025)
Diabetes is a metabolic disorder primarily characterized by persistent hyperglycemia. Diabetes-induced inflammation significantly compromises cardiovascular health, greatly increasing the risk of atherosclerosis. The increasing prevalence of harmful lifestyle habits and overconsumption has contributed substantially to the global rise in diabetes-related cardiovascular diseases, creating a significant economic and healthcare burden. Although current therapeutic strategies focus on blood glucose control and metabolic regulation, clinical observations show that diabetic patients still face persistent residual risk of AS even after achieving metabolic stability. Recent studies suggest that this phenomenon is linked to diabetes-induced trained immunity. Diabetes can induce trained immunity in bone marrow progenitor cells and myeloid cells, thus promoting the long-term development of AS. This article first introduces the concept and molecular mechanisms of trained immunity, with particular emphasis on metabolic and epigenetic reprogramming, which plays a crucial role in sustaining chronic inflammation during trained immunity. Next, it summarizes the involvement of trained immunity in diabetes and its contribution to AS, outlining the cell types that can be trained in AS. Finally, it discusses the connection between diabetes-induced trained immunity and AS, as well as the potential of targeting trained immunity as an intervention strategy. Understanding the molecular mechanisms of trained immunity and their impact on disease progression may provide innovative strategies to address the persistent clinical challenges in managing diabetes and its complications.